Communicative-Based Arabic Language Training in Enhancing Students’ Public Speaking Skills at MAN 1 Kota Padang - Sanra Mahenra Hatoguan Ritonga; Fuji Arifzapni; Amal Syahidin (Journal of Education and Social Culture, 2026)
This study aims to examine the extent to which Arabic language training can improve students’ public speaking skills at MAN 1 Kota Padang. Public speaking is an essential competency that madrasah students need to master in response to increasingly complex and competitive challenges. The Arabic training program was systematically designed to develop students’ confidence, courage, articulation, and oral communication skills. This research employed a qualitative descriptive method with a case study approach. Data were collected through direct observation, in-depth interviews with teachers and students, and documentation of training activities. The findings revealed that Arabic language training had a significant positive impact on students’ public speaking abilities, particularly in terms of self-confidence, speaking fluency, vocabulary mastery, and the ability to organize ideas systematically. The study also found that interactive and practice-based learning methods were more effective than conventional approaches. Therefore, the integration of Arabic language training with public speaking programs should continue to be strengthened in madrasah education.